Episodes of water deprivation enhance daily hypertonic NaCl intake in rats - Pereira, D. T. B. [UNESP]; David, R. B. [UNESP]; Menani, José Vanderlei [UNESP]; Luca Junior, Laurival Antonio de [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2002)
Water and 1.8% NaCl intake was recorded daily in adult male rats (N = 6) submitted to four water deprivations plus four sodium appetite tests, each at the end of each 7-day interval, or in controls (non-deprived, N = 6). Water deprivation was achieved by removing water and 1.8% NaCl for 24 h. Water was then offered for 2 h. At the end of this period, 1.8% NaCl was also offered in addition to water (sodium appetite test). Average daily 1.8% NaCl intake was enhanced from 5.2 ± 1.0 to 15.7 ± 2.5 ml from the first to the fifth week in the experimental group and was unchanged in the control group. Daily water intake was not altered in either group. Thus, repeated episodes of water deprivation enhance daily NaCl intake.
Keywords: Thirst; Salt appetite; Dehydration; Natriuresis